Welcome to OGeek Q&A Community for programmer and developer-Open, Learning and Share
Welcome To Ask or Share your Answers For Others

Categories

0 votes
808 views
in Technique[技术] by (71.8m points)

algorithm - How to solve: T(n) = T(n - 1) + n

I have the following worked out:

T(n) = T(n - 1) + n = O(n^2)

Now when I work this out I find that the bound is very loose. Have I done something wrong or is it just that way?

See Question&Answers more detail:os

与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…
Welcome To Ask or Share your Answers For Others

1 Reply

0 votes
by (71.8m points)

You need also a base case for your recurrence relation.

T(1) = c
T(n) = T(n-1) + n

To solve this, you can first guess a solution and then prove it works using induction.

T(n) = (n + 1) * n / 2 + c - 1

First the base case. When n = 1 this gives c as required.

For other n:

  T(n)
= (n + 1) * n / 2 + c - 1
= ((n - 1) + 2) * n / 2 + c - 1
= ((n - 1) * n / 2) + (2 * n / 2) + c - 1
= (n * (n - 1) / 2) + c - 1) + (2 * n / 2)
= T(n - 1) + n

So the solution works.

To get the guess in the first place, notice that your recurrence relationship generates the triangular numbers when c = 1:

T(1) = 1:

*

T(2) = 3:

*
**

T(3) = 6:

*
**
***

T(4) = 10:

*
**
***
****

etc..

Intuitively a triangle is roughly half of a square, and in Big-O notation the constants can be ignored so O(n^2) is the expected result.


与恶龙缠斗过久,自身亦成为恶龙;凝视深渊过久,深渊将回以凝视…
OGeek|极客中国-欢迎来到极客的世界,一个免费开放的程序员编程交流平台!开放,进步,分享!让技术改变生活,让极客改变未来! Welcome to OGeek Q&A Community for programmer and developer-Open, Learning and Share
Click Here to Ask a Question

...